Analisis Pengendalian Kualitas Produk Coil dengan Pendekatan Metode Six Sigma - Muhamad Subana; Sahrupi Sahrupi; Supriyadi Supriyadi (JiTEKH (Jurnal Ilmiah Teknologi Harapan), 2021)
The cold-rolled coil is a raw material for manufacturing industries such as automotive, household appliances, property, and other industries that use steel plates. The production process during January - June 2020 was not good enough, so that the production process had a defect. The types of defects include stoppage marks, bad trimmer, and over the pickle. This study aims to measure Cpk, and sigma quality levels' process capability and analyze the root causes of low product quality. This study uses the Six Sigma method with the phase Define, Measure, Analyze and Improve. The results showed that Cpk = 1.27, and the sigma value of 3.86. Types of defects that occur are a 72,9% stoppage mark, 17,8% bad trimmer, and 9.3% over the pickle. Recommendations for improvements can be made by conducting training for employees, supervising production employees, periodic maintenance of machines/equipment, and controlling production processes. Six Sigma implementation can identify and improve the quality problems that occur.